2016
DOI: 10.3109/19396368.2016.1156785
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-rich glycoprotein derived peptides affect endometrial angiogenesisin vitrobut has no effect on embryo development

Abstract: (2016) Histidine-rich glycoprotein derived peptides affect endometrial angiogenesis invitro but has no effect on embryo development, Systems Biology in Reproductive Medicine, 62:3, 192-200, DOI: 10.3109/19396368.2016.1156785 To link to this article: https://doi.org/10. 3109/19396368.2016 Histidine-rich glycoprotein (HRG) is an abundant plasma protein involved in multiple biological processes including immunology, vascularisation, and coagulation. These processes are of importance in regulating embryo devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…heterozygous C/T and homozygous T/T carrier status) is associated with a risk of developing gestational hypertensive disorders. Our findings are in line with previous studies demonstrating the T-minor allele (homozygous T/T genotype) to be less favourable, both regarding fertility [ 9 , 16 , 17 ] and the occurrence of recurrent pregnancy loss [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…heterozygous C/T and homozygous T/T carrier status) is associated with a risk of developing gestational hypertensive disorders. Our findings are in line with previous studies demonstrating the T-minor allele (homozygous T/T genotype) to be less favourable, both regarding fertility [ 9 , 16 , 17 ] and the occurrence of recurrent pregnancy loss [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, specific HRG polymorphisms have been associated with recurrent miscarriage [ 13 , 14 ] and infertility [ 9 ] with the possible hypothesis that the amino acid substitution induces a conformational change on the HRG protein which affects its function [ 15 ]. It has thus been further hypothesized that HRG, by regulating angiogenesis, might be an important intermediary for adequate implantation and placentation [ 16 ] . Nonetheless, gene expression studies, validated by proteomics and metabolomics, are required in order to fully understand the underlying regulatory pathways involved in fertility and pregnancy related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Such technology has captured the imagination of practitioners as both a research tool (Costa-Borges et al, 2016;Hardarson et al, 2015;Mölder et al, 2015), comparing embryos resulting from various clinical conditions (Balakier et al, 2016;Gurbuz et al, 2016;Hashimoto et al, 2016;Kaihola et al, 2016;Lindgren et al, 2016), and as a potential prognosticator in clinical practice (Adamson et al, 2016;Chen et al, 2016;Kong et al, 2016;Liu et al, 2016;Milewski et al, 2015;Mizobe et al, 2016;Rubio et al, 2014;VerMilyea et al, 2014;Wu et al, 2016aWu et al, , 2016bYang et al, 2014), although some studies negate this (Freour et al, 2015;Wu et al, 2016aWu et al, , 2016b. Bronet et al (2015) even found distinctive morphokinetic differences between male and female embryos.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is synthesized in liver [24]. Some studies showed that HGR acts in implantation process, embryo development and fertility [25,26]. In their study Lindgren et al were trying to find association between HRG C633T SNP and RSA [24].…”
Section: Molecular Factorsmentioning
confidence: 99%